PEMANFAATAN SUMBER DAYA AIR DI SUB DAS LUBUK PARAKU SUMATERA BARAT - Endes N Dahlan; Rebecca P.; Omo Rusdiana (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Lubuk Paraku sub watershed is located at Batang Arau up-stream with Lubuk Paraku river as the main river. It is an area dominated by protected forest and conservation forest, such as Tahura Dr. Mohammad Hatta. Bukit Barisan I Lubuk Paraku water resource has a good quality and quantity, also fulfilled the environmental quality standards. Lubuk Paraku river is at good category for sustainability resource, it is shown by the coefficient of river regime value. Land cover distribution at Lubuk Paraku sub watershed highly dominated by secondary forest, covering an area of 1.520,15 ha or 61,27%. Lubuk Paraku River has numerous water debits; therefore it has a massive utilization potential for various needs such as household utilization, agriculture, power plants and industrial. Total economic value of water resource in Lubuk Paraku sub watershed is 57.122.973.850,-/year. Keyword:, Hydrology, Lubuk Paraku watershed, Massive utilization, Secondary forest, Total economic value.